2008
DOI: 10.1099/vir.0.2008/001610-0
|View full text |Cite
|
Sign up to set email alerts
|

Human cytomegalovirus infection interferes with major histocompatibility complex type II maturation and endocytic proteases in dendritic cells at multiple levels

Abstract: Human cytomegalovirus (HCMV) infection suppresses cellular immunity and results in viral persistence. Dendritic cells (DCs) are susceptible to HCMV, and the development and immune function of HCMV-infected DCs are impaired in vitro. HCMV-derived proteins interfere with different aspects of major histocompatibility complex type II (MHC II) maturation and function in genetically engineered cellular models. This study directly analysed the effect of HCMV on the MHC II-associated antigen processing and presentatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 36 publications
2
13
0
Order By: Relevance
“…Previous studies have suggested that many viruses, including HIV, have evolved mechanisms to alter antigen processing to their advantage, as a way to escape or direct the immune response (103). Most of these mechanisms affect MHC class I-restricted cellular immune responses; however, mechanisms that alter MHC class II antigen presentation have also been reported (54).…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have suggested that many viruses, including HIV, have evolved mechanisms to alter antigen processing to their advantage, as a way to escape or direct the immune response (103). Most of these mechanisms affect MHC class I-restricted cellular immune responses; however, mechanisms that alter MHC class II antigen presentation have also been reported (54).…”
Section: Discussionmentioning
confidence: 98%
“…Infection of DC was shown to be accompanied by reduced surface expression of MHC-I and -II molecules (50)(51)(52), altered cytokine and chemokine receptor expression (53), and downregulation of molecules required for T and NK cell proliferation (48,50,52). Since DC are important for regulating and controlling T and NK cell responses (54,55) and the latter play a major role in controlling CMV infection (56-60), MuHV8 might infect and functionally paralyze this DC subset by vXCL1 attraction in order to impair antiviral responses.…”
Section: Discussionmentioning
confidence: 99%
“…18 Infection of moDCs has been reported to impair their maturation, inhibiting surface expression of major histocompatibility complex class I and II, costimulatory molecules, and chemokine receptors (ie, CCR1 and CCR5), thus interfering with the development of virus-specific T-cell responses. [19][20][21] Beyond their key role in antigen presentation, DCs may establish a cross-talk with NK cells that reciprocally regulates their Submitted August 9, 2010; accepted October 13, 2010. Prepublished online as Blood First Edition paper, October 28, 2010; DOI 10.1182 DOI 10.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 Inhibition of HLA class I expression is known to be mediated by US2, US3, US6, and US11, 3 whereas the mechanisms underlying the different pattern of HLA class II down-regulation are more complex. 19 The proportion of cells displaying a reduced expression of HLA class I molecules correlated with the number of IE-1/IE-2 ϩ cells in all experiments, and time course analysis revealed that the inhibition of HLA-I expression was detectable at 48 hours (data not shown). The noninfected moDC subset in TB40/E treated cultures, as well as cells incubated with UV-inactivated TB40/E, expressed higher levels of HLA class I molecules than mock moDCs, an effect attributed to the endogenous production of type I IFN-␣, according to previous reports.…”
mentioning
confidence: 99%